2020
DOI: 10.1016/j.jclepro.2019.119838
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to measure product quality in sustainable supplier selection

Abstract: A gap remains due to the intangible and qualitative criteria used to measure product quality for supplier evaluation and selection. Improving product quality is a crucial strategy for achieving reduce, reuse, recycle, and recovery. Quality characteristics are described as functional relationships (called profiles), and with the advancements in measurement technology, high dimensional data are collected. Nonetheless, prior studies have not addressed sustainable supplier selection where a nonlinear profile chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Also, considering a real case study, the authors employed the graded mean integration representation method to prioritize the suppliers. Negash et al ( 2020 ) examined the sustainable supplier selection applying the Monte Carlo simulation approach considering product quality. The authors showed the model applicability by implementing in a real-life case study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, considering a real case study, the authors employed the graded mean integration representation method to prioritize the suppliers. Negash et al ( 2020 ) examined the sustainable supplier selection applying the Monte Carlo simulation approach considering product quality. The authors showed the model applicability by implementing in a real-life case study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Selecting the most sustainable suppliers is a complicated decision of managers (Xie et al, 2011). Selecting proper suppliers improves planning (T€ urk et al, 2017), quality of goods and services (Negash et al, 2020), and customer satisfaction (Lewin, 2009). On the other hand, as is seen in the case study, in the real world, there might be binary data, which managers have to deal with it.…”
Section: Managerial Implicationsmentioning
confidence: 97%
“…Agreement and work with reliable suppliers is also a complicated and significant strategic decision for managers and decision-makers of SCs (Dey et al, 2015;Xie et al, 2011). Suppliers assessment affects inventory planning (T€ urk et al, 2017), production planning and control (Che, 2017;Hlioui et al, 2017;Nguyen and Chen, 2018), financial performance (Yu and Huo, 2019), quality management (Negash et al, 2020), risk management (Kaur and Singh, 2021;Rao et al, 2017;Wong, 2020), purchasing management (Bolander et al, 2018) and customer satisfaction (Lewin, 2009;Saor ın-Iborra and Cubillo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For many buyer companies, important criteria for Engineering Management in Production and Services assessing the efficiency of suppliers are their response time to complaints or technical problems related to the use (raw materials, parts or infrastructure elements). Furthermore, many companies, especially international corporations, by promoting the concept of sustainability, wanting to further reduce the risk associated with suppliers, pay attention to such aspects as pro-ecological activities or contractor's ethics (Govindan et al, 2015;Guarnieria &Trojan, 2019;Kartika et al, 2020). Environmental management systems for compliance with the requirements of the ISO 14001 standard, as well as health and safety management systems based on the guidelines of the ISO 45001 standard, are also increasingly important in the evaluation of suppliers (Yan et al, 2017).…”
Section: Supplier Evaluation Criteriamentioning
confidence: 99%